2020
DOI: 10.1093/ijpor/edaa036
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay of Online Network Homogeneity, Populist Attitudes, and Conspiratorial Beliefs: Empirical Evidence From a Survey on German Facebook Users

Abstract: Social networking sites are suspected to impede the communication between members of different political camps and thereby increase network homogeneity. This homogeneity can be a result of humans’ tendency to process information in confirmatory ways—a characteristic which is also ascribed to populist citizens and those who hold conspiratorial beliefs. It is hypothesized that populist views and conspiratorial beliefs are associated with higher exposure to like-minded information within Facebook. An online surve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…While social media platforms may contain mixed-attitudinal communities where users can be exposed to diversified viewpoints and exchange their ideas freely (Mutz, 2006), most individuals prefer to engage with like-minded social media environments (Stroud, 2010). In this study, social network homogeneity refers to the extent to which users are more likely to be exposed to information that is consistent with their own views within online networks, rather than non-like-minded information (Cargnino, 2021). Social network homogeneity sets the conditions for in-group discussions.…”
Section: The Moderating Role Of Network Homogeneitymentioning
confidence: 99%
“…While social media platforms may contain mixed-attitudinal communities where users can be exposed to diversified viewpoints and exchange their ideas freely (Mutz, 2006), most individuals prefer to engage with like-minded social media environments (Stroud, 2010). In this study, social network homogeneity refers to the extent to which users are more likely to be exposed to information that is consistent with their own views within online networks, rather than non-like-minded information (Cargnino, 2021). Social network homogeneity sets the conditions for in-group discussions.…”
Section: The Moderating Role Of Network Homogeneitymentioning
confidence: 99%
“…Research shows positive relations between populist attitudes and CBs (Cargnino, 2021;Eberl et al, 2021). This relationship, however, turned out to be more complicated in a Chinese study by Guan and Yang (2020), who identified two subtypes of populism (right-vs. responsibility-oriented) and two subtypes of conspiracy beliefs (prosystem vs. anti-system).…”
Section: Political Factorsmentioning
confidence: 99%